Feeling the narrative control(ler): Casual art games as trauma therapy - Austin, Hailey J.; Cooper, Lydia R. (Replay. The Polish Journal of Game Studies, 2022)
Through a combination of aesthetics and game mechanics, casual art games offer unique engagements with trauma, allowing players to practice grief or empathise with the traumatic experiences of others. Both “Spiritfarer” (Thunder Lotus Games 2020) and „Mutazione” (Die Gute Fabrik 2019) utilise similar aesthetics (2D art, pastel colours and calming music) alongside agency-driven gameplay mechanics (choosing when to let spirits go or how to react to a character’s trauma) that create a safe space. This is possible because neither game is competitive, nor does it allow the player to lose. Instead, agency is given to the player through narrative choice and exploration of the beautiful storyworld. We argue that games like “Spiritfarer” and “Mutazione” can be used as models for the further development of casual art games that can be used as art therapy through their emotional connections embedded in both the aesthetics and gameplay.